Online Shopping Therapy: If You Want to Be Happy, Shop around. Issue 3 (27th May 2022) - Zulauf, Katrin; Wagner, Ralf
Abstract: This paper examines the relationships between online therapeutic shopping motivation, crisis-coping shopping, and therapeutic shopping purchases in disruptive situations. It explicitly addresses the research question of how online shopping motivation and crisis-coping shopping affect therapeutic shopping purchases. Empirical evidence was obtained in Europe and Latin America. We used partial least squares modeling and multigroup analysis to compare consumers' culture-driven responses to crisis. The effect of crisis-coping shopping is almost three times stronger than the effect of online therapeutic shopping motivation on therapeutic shopping purchases. This study investigates the concepts of hedonic shopping and retail therapy in the online environment and disruptive situations by examining therapeutic shopping purchases. Cultural differences are highlighted in relation to purchases made to regulate mood during a crisis. Finally, this study examines the roles of retail therapeutic motivation and crisis-coping online shopping and discusses the implications for consumers, managers, and future research.